NARRATIVE AND META‐ANALYTIC REVIEW OF INTERVENTIONS AIMING TO IMPROVE MATERNAL–CHILD ATTACHMENT SECURITY. Issue 4 (25th June 2015) - Letourneau, Nicole; Tryphonopoulos, Panagiota; Giesbrecht, Gerald; Dennis, Cindy‐Lee; Bhogal, Sanjit; Watson, Barry
ABSTRACT Early secure maternal–child attachment relationships lay the foundation for children's healthy social and mental development. Interventions targeting maternal sensitivity and maternal reflective function during the first year of infant life may be the key to promoting secure attachment. We conducted a narrative systematic review and meta‐analysis to examine the effectiveness of interventions aimed at promoting maternal sensitivity and reflective function on maternal–child attachment security, as measured by the gold standard Strange Situation (M. Ainsworth, M. Blehar, B. Waters, & S. Wall, 1978) and Q‐set (E. Waters & K. Deane, 1985). Studies were identified from electronic database searches and included randomized or quasi‐randomized controlled parallel‐group designs. Participants were mothers and their infants who were followed up to 36 months' postpartum. Ten trials, involving 1, 628 mother–infant pairs, were included. Examination of the trials that provided sufficient data for combination in meta‐analysis revealed that interventions of both types increased the odds of secure maternal–child attachment, as compared with no intervention or standard intervention (n = 7 trials; odds ratio: 2.77; 95% confidence interval: 1.69, 4.53, n = 965). Of the three trials not included in the meta‐analyses, two improved the likelihood of secure attachment. We conclude that interventions aimed at improving maternal sensitivity alone or in combination with maternal reflection, implemented in the first year of infants' lives, are effective in promoting secure maternal–child attachments. Intervention aimed at the highest risk families produced the most beneficial effects.